THE EFFECT OF RESISTANCE TRAINING ON THE DEVELOPMENT OF SOME PHYSICAL ATTRIBUTES AND THE COMPLETION OF THE 800-METER RUN FOR ROOKIES (ResearchJet Journal of Analysis and Inventions, 2023)
The importance of the research lies in the use of resistance exercises As for the research problem: There is a weakness in the use of special exercises in the style of resistance training, as well as a lack of interest in resistance exercises when developing physical qualities, especially muscle strength, which is one of the reasons for the low level of endurance for runners, which suffers from the level of achievement of the 800-meter run.